Resistensi Dakwah Salafi terhadap Amal Usaha Muhammadiyah di Sidoarjo - Zaini Tamin AR; Riduwan Riduwan (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2020)
The infiltration of the Salafis into the Muhammadiyah organization became a continuing reality. This reality is driven by symptoms of the strengthening of the concept of salafism in the organization that founded by KH. Ahmad Dahlan. This study seeks to analyze the Salafi da’wah against the Charitable Business of Muhammadiyah in Taman, Sidoarjo, which is always resistant. This research uses a qualitative method with a naturalistic interpretive approach. The findings of this study reveal that Salafis offer